The "contact hypothesis" and attitudes toward same-sex parenting - Costa, Pedro Alexandre (2015)
“The contact hypothesis” refers to the value of heterosexuals’ interpersonal contact with gay men and lesbians in lowering negative attitudes toward them. With the increasing number of same-sex parented families worldwide, in spite of a generalized lack of appropriate social and legal protection, the issue of attitudes toward gay and lesbian parents gains special relevance. A sample of 1690 Portuguese heterosexual individuals were asked about their interpersonal contact experiences with gay men and lesbians, their attitudes toward them and toward same-sex parenting. Results revealed that women and non-religious participants were significantly more likely to have gay and lesbian acquaintances and friends, feel more comfortable in their company, and hold less negative attitudes toward gay men and lesbians, and gay and lesbian parenting. A path analysis model revealed that interpersonal contact experiences were not directly linked to attitudes toward same-sex families, but were mediated by homonegativity and comfort with gay men and lesbians. These findings extend previous knowledge about the value of interpersonal contact, by highlighting the roles of homonegativity and positive affect as mediators of contact experiences on attitudes toward same-sex parented families.